Evaluate severe acute respiratory syndrome coronavirus 2 infectivity by pseudoviral particles. Issue 9 (25th April 2020) - Pu, Tao; Ding, Chen; Li, Yadong; Liu, Xiaojuan; Li, Haiwei; Duan, Jinmei; Zhang, Heng; Bi, Yanwei; Cun, Wei
Abstract: Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in humans in late 2019, it has rapidly spread worldwide. To identify the biological characteristics of SARS‐CoV‐2 in a normal laboratory environment (biosafety level 2 [BSL‐2]), a lentiviral‐based nucleocapsid was used to carry the spike protein of SARS‐CoV‐2 onto the surface of pseudoviral particles as a surrogate model to evaluate the infective characterization of SARS‐CoV‐2. This study indicated that SARS‐CoV‐2 has extensive tissue tropism for humans and may infect monkeys and tree shrews but not rodents. More importantly, the use of pseudoviral particles in this study allows rapid assessment of neutralizing antibodies in serum in a BSL‐2 laboratory. This study will provide a quick and easy tool for evaluating neutralizing antibodies in the serum of recovering patients and assessing the potency of candidate vaccines. Highlights: Lentiviral‐based pseudo‐particles with SARS‐CoV‐2 spike proteins (SaCaov2pp) were produced to rapid evaluate SARS‐CoV‐2 infectivity and neutralizing antibodies titer in a normal laboratory environment. SaCoV2pp has extensive tissue tropism for primates but not for human diploid embryo lung cell strain or monkey liver cell line. The rhesus monkey neutralizing serums for SaCoV2pp has little cross‐reactivity with SaCoV1pp.